Modifiable risk factors and cardiovascular outcomes - Figtree, GA; Gray, MP; Channon, KM (Massachusetts Medical Society, 2023)
To the Editor: The results of an investigation of risk factors on the incidence of cardiovascular disease and death from any cause, as reported by Magnussen et al. on behalf of the Global Cardiovascular Risk Consortium (Oct. 5 issue), show that these risk factors accounted for a population-attributable fraction of the 10-year incidence of cardiovascular disease of 52.6% among men and 57.2% among women. The factors that were investigated are five modifiable risk factors (body-mass index, systolic blood pressure, the level of non–high-density lipoprotein [HDL] cholesterol, current smoking, and diabetes). It is disappointing that current smoking and diabetes were selected…